2002
DOI: 10.1021/jp020262i
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity of Polyelectrolyte Solutions in the Semidilute and Concentrated Regime:  The Role of Counterion Condensation

Abstract: The d.c. electrical conductivity of polyacrylate sodium salt and poly(acrylic acid) aqueous solutions of different molecular weights from 2 to 200 kD has been investigated in a wide range of polymer concentration, covering both the semidilute (unentangled and entangled) and concentrated regimes. The data have been analyzed on the basis of a modified version of the Manning theory of counterion condensation, to cover the semidilute regime, taking into account scaling arguments recently proposed by Dobrynin et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 25 publications
6
71
0
Order By: Relevance
“…We confine ourselves to one's own measurements [4,5,8,12], but in the recent literature many other appropriate examples can be easily found.…”
Section: Comparison With Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We confine ourselves to one's own measurements [4,5,8,12], but in the recent literature many other appropriate examples can be easily found.…”
Section: Comparison With Experimentsmentioning
confidence: 99%
“…In this review, we summarize the main results and collect the relevant expressions governing the electrical conductivity of a polyelectrolyte solution in different experimental conditions, on the basis of a series of our own papers, appeared in the last few years [4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A survey of the literature indicated that the influences of polyelectrolyte concentration, polyelectrolyte molecular weight, medium, and temperature on counterion condensation in salt-free polyelectrolyte solution have been fairly investigated [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…These interactions are strongly sensitive to some parameters such as the chain length, the charge density, the polyelectrolyte concentration, the counterion type, the ionic strength, the solvent polarity, etc. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Perhaps the most significant parameter affecting the solution properties of a polyelectrolyte is the linear charge density whose importance has been promoted by Manning in his counterion condensation theory [24,25].…”
Section: Introductionmentioning
confidence: 99%